2021
DOI: 10.1111/vsu.13564
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and diagnostic findings, treatment, and short‐ and long‐term survival in horses with peritonitis: 72 cases (2007‐2017)

Abstract: To identify etiology, clinical findings, diagnostic results, treatment, and short-and long-term survival and to report factors associated with nonsurvival and survival in horses with peritonitis. Study design: Retrospective study. Animals: Horses (n = 72). Methods: Medical records at William R. Pritchard Veterinary Medical Teaching Hospital from 2007-2017 were reviewed for horses diagnosed with peritonitis. The essential inclusion criterion was a peritoneal nucleated cell count of ≥25 000 cells/μL. Gastrointes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
1
4
0
3
Order By: Relevance
“…In the current case, minimally invasive transabdominal drainage of an intrasplenic abscess caused by Clostridium perfringens after trauma from a sharp metallic object led to complete healing and return to the previous level of performance. results of abdominocentesis revealed severe non-septic peritonitis (Arndt et al, 2021). Although non-specific per se, all these findings are in accordance with previously described cases of intrasplenic abscess formation (Alsop et al, 2007;Coleman & Schmitz, 2019;Rosso et al, 2012;Thomson et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the current case, minimally invasive transabdominal drainage of an intrasplenic abscess caused by Clostridium perfringens after trauma from a sharp metallic object led to complete healing and return to the previous level of performance. results of abdominocentesis revealed severe non-septic peritonitis (Arndt et al, 2021). Although non-specific per se, all these findings are in accordance with previously described cases of intrasplenic abscess formation (Alsop et al, 2007;Coleman & Schmitz, 2019;Rosso et al, 2012;Thomson et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…At the time of presentation, haematology revealed severe leucocytosis, neutrophilia, lymphopenia, hyperproteinaemia and hyperfibrinogenaemia, which is consistent with chronic inflammation. The results of abdominocentesis revealed severe non‐septic peritonitis (Arndt et al, 2021). Although non‐specific per se, all these findings are in accordance with previously described cases of intrasplenic abscess formation (Alsop et al, 2007; Coleman & Schmitz, 2019; Rosso et al, 2012; Thomson et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the time from admission to surgery was decreased from a median of 1.2 to 0.3 days, the risk of intraoperative euthanasia decreased from 52% (11/21) to 17% (1/6), and the chance of survival in horses where resection was performed increased from 33% (3/9) to 100% (5/5) ( p = 0.030) 36 . As idiopathic peritonitis generally has a high survival rate to discharge without surgery, 8,37,38 decision making (to decide whether to perform surgery) in horses with peritonitis is difficult. A previous study identified no signs of abdominal pain, normal intestinal borborygmi, normal faeces, no nasogastric reflux, normal colour of PF and normal findings on palpation per rectum to be the most important variables indicating survival without surgery in horses with peritonitis 37 .…”
Section: Discussionmentioning
confidence: 99%
“…This retrospective study by Stefanie Arndt and co‐workers at the University of California‐Davis, USA, investigated clinical and diagnostic findings, treatment, and short‐ and long‐term survival in 72 horses with peritonitis .…”
Section: Survival In Horses With Peritonitismentioning
confidence: 99%